2014
DOI: 10.4103/2230-8229.128775
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and associated cardiovascular risk factors in Central India

Abstract: Objectives:To study the difference in the prevalence of hypertension and associated risk factors in urban and rural populations and the association of hypertension with various determinants.Materials and Methods:A community-based cross-sectional study was conducted in 48 villages and 15 urban wards of Jabalpur District of Central India. Nine hundred and thirty-nine individuals aged 20 years and above (624 from rural areas and 315 from urban areas) were included in the study. The prevalence of hypertension and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
45
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 21 publications
15
45
1
4
Order By: Relevance
“…18 Hypertension prevalence was similar in pure veg and mixed diet taking individuals in this study, similar result were found by Bhadoria et al in rural and urban population who found no significant effect of vegetarian diet and mixed diet on hypertension. 27 Similar findings was also observed by Radhakrishnan et al among tribals of Tamil Nadu. 20 In this study family history was significantly associated with hypertension.…”
Section: Discussionsupporting
confidence: 79%
“…18 Hypertension prevalence was similar in pure veg and mixed diet taking individuals in this study, similar result were found by Bhadoria et al in rural and urban population who found no significant effect of vegetarian diet and mixed diet on hypertension. 27 Similar findings was also observed by Radhakrishnan et al among tribals of Tamil Nadu. 20 In this study family history was significantly associated with hypertension.…”
Section: Discussionsupporting
confidence: 79%
“…[5,6] Age more than 45 years was associated with risk of HTN in our study which was similar to other studies. [6,9] Alcohol intake and tobacco usage were not associated in our study with HTN which was very much contrast to other studies.…”
Section: Discussionsupporting
confidence: 82%
“…[5,12,13] A few studies conducted in rural areas of Jaipur by Kumar et al in Central India by Bhadoria et al in rural Delhi by Kishore et al and in Maharashtra by Todkar et al found a prevalence of HTN as 13.17%, 14.8%, 14.1% and 7.24%, respectively, which were very much lower compared to our study. [6,7,9,14] This increase in the prevalence of HTN was may be due to rural population changing their traditional lifestyle to urban lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the study subjects, 24.9% of them who were hypertensive were found to be either overweight or obese with an odds ratio of 1.4. Similar findings were seen in studies conducted by and Bhadoria et al and Galav et al 14,24 As the individual tends to gain more weight, greater is the risk of increasing blood pressure. Central obesity is one of the direct correlates of high blood pressure.…”
Section: Figure 1: Prevalence Of Hypertension Among the Study Populatsupporting
confidence: 77%